Ukrainian Practice of Virtual Diplomacy - Tereshchuk, Vitaliy (Historia i Polityka, 2016)
The article reveals the processes of transformation of diplomatic activity of the state under the influence of the Internet information and communication services. Relevance of this problem is caused by new opportunities and challenges the state diplomatic service faces under conditions of existence of such cross-border communication media as the Internet. In particular, it includes the possibilities of establishing the channels of target audiences direct informing abroad and operational informing of the world community as for rather topical issues of the state foreign policy. In the present political conditions and limited (compared with Russia) media opportunities it is more important for Ukraine to use the Internet to deliver its position on urgent problems of its domestic and foreign policy.